Some aspects on the biology, distribution and fishery of the snapping shrimp (Alpheus cf. euphrosyne) in Talabong mangrove forest, Bais City, Negros Oriental, Philippines - Vergara, Christopher John C.
Distribution and physic-chemical characteristics of the habitat of snapping shrimps using the quadrat method was determined during the months of June, July and August 2015 at the Talabong Mangrove Forest, Bais City, Negros Oriental, Philippines. Moreover, its fishery was also determined. A total of 203 snapping shrimps were collected during the sampling period. Results showed that the morphology of the species in this study was very similar to that shrimp. The snapping shrimps had a mean total length (TL) of 68.86+7.004 mm. The female (TL, 71.77+6.283 mm) snapping shrimps are relatively bigger than the male (TL, 66.83+5.789 mm) snapping shrimps. Furthermore, the snapping shrimps were observed to aggregate in certain location of the mangrove forest and prefer a mangrove root vegetation which is primarily dominated by prop roots (12.61 burrows 25 m2) and a combination of pneumatophores and prop roots (14.79 burrows 25 m-2). It was also observed that the physic-chemical characteristics during sampling, specifically dissolved oxygen (6.22+0.021 mg l-1), pH (6.85+0.052), temperature (30.18+0.21 0C), and salinity (35 ppt), in the mounds of snapping shrimps were relatively similar throughout the mangrove forest. Also, the snapping shrimps prefer a substrate characteristics of sandy clay loam. The snapping shrimps of Talabong Mangrove Forest were not overexploited by the locals and that it does not experience pressure from overfishing since there was a very low catch per unit effort (160.38 g h-1) and the catch were mostly represented by relatively big individuals (TL, 63.6-77.0 mm).